ENHANCEMENT OF THAI TEACHERS’ COMPETENCIES IN THAI EDUCATION 4.0 - Ruankum, Nutakarn; Suthasinobol, Kittichai (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2022)
Enhancement of Thai teachers’ Competencies in Thai Education 4.0 is a very important issue in education management at the present era which has to enhance teachers’ competencies in the education field to be consistent with Thai Education 4.0 following the concept of "stability, prosperity, sustainability." This framework is a goal of development in all areas. However, bringing the Thai education system 4.0 to be an important mechanism that enhances quality personnel and human resources, increases the potential to drive development towards the goal, strengthens students’ ability to think in problem-solving, and produces and creates product skillfully. Therefore, teacher development is important, like the first brick that must be laid with knowledge, attributes, and ability to be the foundation of the next transformation. In considering the teacher competencies, which consisted of core and functional competencies including the enhancement of teacher skills based on the C-Teacher concept and the role of E-Teacher, which is an overview of the approach to developing teachers in the 21st century in becoming qualified and competent persons in accordance with the Thai Education 4.0 Framework. It was found that learners’ life skills, knowledge and morals should be developed with the adjustment of teaching and learning to be more appropriate and tangible. Thai Education 4.0 found that Enhancement of Thai Teachers’ Competency have the ability to develop learners to have skills in life. Having knowledge of virtue, teachers need to adjust their teaching and learning to suit the situation appropriately and more concretely. Thai Education 4.0 will be successful according to the conceptual framework and desired goals.